COSMOPOLITANISM, GLOBAL ETHIC, AND INTERRELIGIOUS DIALOGUE - Bombongan, Dominador (Journal of Dharma, 2008)
We live in a world of “‘overlapping communities of fate’ where nations’ destiny is significantly intertwined,”argues, David Held. Indeed, our world has become so globalized that concerns have been raised on how to make sense of (a) the scope and extent of justice as well as duties across nation-states, (b) the coverage of transnational political and social realities, (c) the limit of complex affiliations, meaningful attachments and multiple allegiances to issues, people and places, and (d) the parameters of global democracy and world citizenship. The dramatic transformations that the processes of globalization have brought about, call for a new way of relating to the socio-economic, cultural as well as political realities of our times.